2022
DOI: 10.1002/cjoc.202200354
|View full text |Cite
|
Sign up to set email alerts
|

Cascade Synthesis of Luminescent Difluoroboron Diketonate Compounds forRoom‐TemperatureOrganic Afterglow Materials

Abstract: Difluoroboron β-diketonate (BF 2 bdk) compounds represent an important class of luminescent materials, whereas their synthesis requires multiple steps, which restrict their application in diverse fields. Here we report a cascade reaction to prepare BF 2 bdk from aromatic ketones, carboxylic acids, trifluoroacetic anhydride and boron trifluoride diethyl etherate. The cascade reaction is very simple and straightforward to produce BF 2 bdk with desired functional groups in reasonable isolation yields. Further, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…Recently, two-component dopant-matrix design strategies developed by us and others have emerged as an important pathway for the fabrication of high-performance organic RTP materials. [2,23,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Besides the molecular design of luminescent dopants, organic matrices also play an essential role in material preparation as suitable organic matrices can modulate the triplet excited state properties of luminescent dopants. It has been reported that crystalline or glassy matrices can provide rigid microenvironments for luminescent dopants to suppress the nonradiative decay of dopants' triplet excited states.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two-component dopant-matrix design strategies developed by us and others have emerged as an important pathway for the fabrication of high-performance organic RTP materials. [2,23,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Besides the molecular design of luminescent dopants, organic matrices also play an essential role in material preparation as suitable organic matrices can modulate the triplet excited state properties of luminescent dopants. It has been reported that crystalline or glassy matrices can provide rigid microenvironments for luminescent dopants to suppress the nonradiative decay of dopants' triplet excited states.…”
mentioning
confidence: 99%
“…It has been reported that crystalline or glassy matrices can provide rigid microenvironments for luminescent dopants to suppress the nonradiative decay of dopants' triplet excited states. [30][31][32][33][34][35][36][37][38] Hydrogen bonding interactions between matrices and dopants have been found to significantly inhibit the nonradiative decay of the triplet excited states of luminescent dopants. [39,40] Besides suppressing nonradiative decay, organic matrices can also facilitate intersystem crossing (ISC) of luminescent dopants by intermolecular charge transfer, [2,41,42] mediation of matrix's T 1 states, [31,43] dipole-dipole interactions, [23,44] and sensitization and energy transfer.…”
mentioning
confidence: 99%
“…The fluoranthene‐containing BF 2 bdk compound, YNBF 2 , was synthesized via cascade reactions developed in our group [51–55] . This reaction is very simple, practical and straightforward, using the one‐pot reaction of fluoranthene, acetic anhydride and boron trifluoride diethyl etherate.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, two-component strategies have been found to allow a flexible choice of both organic matrices and luminescent dopants to construct RTP and organic afterglow materials with diverse compositions and structures. ,,, When one component (either dopants or matrices) is fixed, systematic studies by varying the other component lead to a deep understanding of the photophysical mechanism of dopant–matrix systems; this is very important for fabricating high-performance RTP and afterglow materials. There are representative studies for the fabrication of high-performance RTP and afterglow materials in two-component systems.…”
Section: Introductionmentioning
confidence: 99%
“…When the organic matrices are polymers, the dopant–matrix design strategy leads to the formation of polymer-based RTP and organic afterglow materials with excellent flexibility and mechanical properties. Poly­(methyl methacrylate) (PMMA) matrices have been mostly used because PMMA is inexpensive, transparent, and soluble in many organic solvents. Diverse PMMA-based RTP materials with anticounterfeiting and data encryption functions have been reported, and solution casting is the most applied technique to fabricate these materials. Poly­(vinyl alcohol) (PVA) matrices have been reported to provide a rigid microenvironment for and inhibit the nonradiative decay of triplet excited states of luminescent dopants, giving rise to intriguing color-tunable RTP systems and others. Water processability is a unique advantage of PVA matrices different from other synthetic polymers. Polylactic acid (PLA)-based and end-capped systems have been reported to show film-forming properties and hypoxia sensing functions via fluorescence/phosphorescence dual emission behaviors. , Our recent studies showed that the macromolecular self-assembly strategy and photopolymerization technique can also be used to fabricate high-performance RTP materials. , Besides, polystyrene, polyacrylonitrile, poly­(ethylene- co -vinyl acetate), and other polymers have been shown to suppress the nonradiative decay and quenching of luminescent dopants for constructing organic RTP materials. Despite the diverse compositions of the above polymer-based materials, it is found that these materials mainly follow the RTP mechanism.…”
Section: Introductionmentioning
confidence: 99%